Design considerations for developing a new, ultra-high precision feeder for micro-sheet-forming applications. (14th July 2009) - Razali, Akhtar; Qin, Yi; Harrison, Colin; Brockett, Andrew
A recent review of micro-forming research and technological development suggested that the trend of the development is focused more on the manufacturing processes, machines and tooling, with efforts on the precision material handling being insufficient. Most of the developed machines were based on stand-alone concepts that do not support efficient integration to make them fully automated and integrated. Material feeding, in most cases, was not of sufficient precision and reliability for high throughput manufacturing applications. Precision feeding is necessary to ensure that micro-parts can be produced with sufficient accuracy, especially in multi-stage forming, while high-speed feeding is a necessity to meet production-rate requirements. Therefore, the design of a new high-precision and high-speed feeder for micro-forming is proposed. Several possible approaches are examined with a view to establishing feasible concepts. Based on the investigation, several concepts for thin sheet-metal feeding for micro-forming have been generated, these being argued and assessed with appropriate applied loads and force analysis. These form a basis for designing a new feeder.